Hydrothermal alteration and mineralization of Baiyun gold deposit in Liaodong Peninsula, North China Craton. (22nd December 2020) - Zhang, Zhichao; Wang, Yuwang; Li, Dedong; Wang, Wei; Li, Shenghui; Qiu, Jinzhu; Lai, Chunkit; Li, Xiang
Abstract : Baiyun deposit is a large gold deposit in the Liaodong Peninsula (North China Craton), containing over 31.7 t of gold. Silicic alteration, K‐feldspar alteration, and pyritization are well developed and closely related with mineralization in Baiyun deposit. Based on field and optical microscopic observations, the alteration styles include quartz + K‐feldspar zone, pyrite + sericite +quartz zone, and chlorite zone from orebody outward. In this study, the quartz, K‐feldspar, and pyrite of pre‐ore, syn‐ore stages 1 and 2 were selected for LA‐ICP‐MS trace element analysis and electron probe microanalysis (EPMA) to reveal the alteration‐mineralization link. Results show that the albite was altered to mainly K‐feldspar and minor secondary quartz at syn‐ore stage 1. Fluid‐rock reaction of the silicic‐potassic alteration may have decreased the fluid oxygen fugacity ( f O2 ), which triggered the gold precipitation. Most of invisible gold occurred in the form of solid solution. At syn‐ore stage 2, albite altered to mainly quartz and minor K‐feldspar. The syn‐ore stage 1 K‐feldspar also altered to minor secondary quartz at syn‐ore stage 2. In addition, the release of sulphur from the syn‐ore stage 1 pyrite was likely another trigger for the gold precipitation. Most of syn‐ore stage 2 invisible gold occurred as nano‐particles. The ore‐forming fluids consist mainly of primary magmatic fluids mixed with minor metamorphic fluids. The ore metals may have sourced mainly from the magmatic fluid and the sillimanite‐mica schist of the Gaixian Formation. Abstract : Alteration zonation of Baiyun gold deposit is clarified. Silicic–potassic alteration mechanism is reflected by in‐situ trace elements. The relationship between alteration and mineralization is revealed.